ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP TERHADAP MATERI RELASI DAN FUNGSI - Kiki Patmala; Selvia Erita (Universitas Muhammadiyah Metro, 2024)
The understanding of mathematical concepts is highly essential for students in mathematics learning. This is because mathematics is a subject that involves numerous concepts. Conceptual understanding relates to the ability to comprehend comprehensive and functional mathematical ideas. This research aims to investigate students' mathematical conceptual understanding in the context of relations and functions. The research is of a qualitative nature with a descriptive approach. The subjects of this study consist of 25 eighth-grade students from the Granada class at SMP IT Sungai Penuh. The results of the study reveal that students face challenges in applying mathematical problem-solving concepts and developing necessary conditions in the context of relations and functions. In conclusion, students possess a